The effect of a micronutrient powder home fortification program on anemia and cognitive outcomes among young children in rural China: a cluster randomized trial - Renfu Luo; Ai Yue; Huan Zhou; Yaojiang Shi; Linxiu Zhang; Reynaldo Martorell; Alexis Medina; Scott Rozelle; Sean Sylvia (BMC, 2017)
Abstract Background Anemia early in life has been associated with delayed cognitive and motor development. The WHO recommends home fortification using multiple micronutrient powders (MNPs) containing iron as a strategy to address anemia in children under two. We evaluated the effects of a program freely distributing MNP sachets to caregivers of infants in rural China. Methods We conducted a cluster-randomized controlled trial in Shaanxi province, enrolling all children aged 6-11 months in target villages. Following a baseline survey, investigators randomly assigned each village/cluster to a control or treatment group. In the treatment group, caregivers were instructed to give MNPs daily. Follow-up was after 6, 12, and 18 months of intervention. Primary outcomes were hemoglobin concentrations and scores on the Bayley Scales of Infant Development. Results One thousand, eight hundred and-two eligible children and their caregivers were enrolled. At baseline 48% (870) of children were anemic and 29% (529) were developmentally delayed. Six hundred and-ten children (117 villages) were assigned to the control group and 1192 children (234 villages) were assigned to the treatment group. Assignment to the treatment group was associated with an improvement in hemoglobin levels (marginal effect 1.77 g/L, 95% CI 0.017-3.520, p-value = 0.048) and cognitive development (marginal effect 2.23 points, 95% CI 0.061-4.399, p-value = 0.044) after 6 months but not thereafter. There were no significant effects on motor development. Zero effects after the first 6 months were not due to low compliance, low statistical power, or changes in feeding behavior. Hemoglobin concentrations improved in both the treatment and control groups over the course of the study; however, 22% (325) of children remained anemic at endline, and 48% (721) were cognitively delayed. Conclusions Providing caregivers with MNP sachets modestly hastened improvement in hemoglobin levels that was occurring absent intervention; however, this improvement did not translate into improved developmental outcomes at endline. Trial registration ISRCTN44149146 ; prospectively registered on 15th April 2013.